2017
DOI: 10.1101/128587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On statistical modeling of sequencing noise in high depth data to assess tumor evolution

Abstract: One cause of cancer mortality is tumor evolution to therapy-resistant disease. First line therapy often targets the dominant clone, and drug resistance can emerges from preexisting clones that gain fitness through therapy-induced natural selection. Such mutations may be identified using targeted sequencing assays by analysis of noise in high-depth data. Here, we develop a comprehensive, unbiased model for sequencing error background. We find that noise in sufficiently deep DNA sequencing data can be approximat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The TME often comprises only a small fraction of the tumor and bulk RNA-seq reads; however, the precise identification of small TME cellular subsets, such as natural killer (NK) cells, is essential because they significantly impact therapeutic response (legend continued on next page) ll Article and clinical outcome across diverse diseases. Addressing technical noise is essential during cellular deconvolution to accurately identify cell subsets from bulk RNA-seq (Ding et al, 2015;Rabadan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The TME often comprises only a small fraction of the tumor and bulk RNA-seq reads; however, the precise identification of small TME cellular subsets, such as natural killer (NK) cells, is essential because they significantly impact therapeutic response (legend continued on next page) ll Article and clinical outcome across diverse diseases. Addressing technical noise is essential during cellular deconvolution to accurately identify cell subsets from bulk RNA-seq (Ding et al, 2015;Rabadan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We note that previous work has shown that DNA sequencing count data is well-represented by a negative binomial distribution (Rabadan et al, 2018).…”
Section: Latent Subcountsmentioning
confidence: 70%
“…For each residue, all codon changes included in the library design were identified in the mapped reads and counted. To distinguish a true amino acid change from sequencing errors, background noise was modeled by aggregating negative binomial distributions 40 . Briefly, if the total number of reads for a locus in sample I is N i among which n i reads harbor the amino acid change of interest, the distribution of n i follows a binomial distribution given N i and a priori probability of occurrence as error.…”
Section: Saturation Mutagenesis Analysismentioning
confidence: 99%